Chemical inhibition of bacterial protein tyrosine phosphatase suppresses capsule production. - Alistair J Standish; Angela A Salim; Hua Zhang; Robert J Capon; Renato Morona (PLoS ONE, 2012)
Capsule polysaccharide is a major virulence factor for a wide range of bacterial pathogens, including Streptococcus pneumoniae. The biosynthesis of Wzy-dependent capsules in both gram-negative and -positive bacteria is regulated by a system involving a protein tyrosine phosphatase (PTP) and a protein tyrosine kinase. However, how the system functions is still controversial. In Streptococcus pneumoniae, a major human pathogen, the system is present in all but 2 of the 93 serotypes found to date. In order to study this regulation further, we performed a screen to find inhibitors of the phosphatase, CpsB. This led to the observation that a recently discovered marine sponge metabolite, fascioquinol E, inhibited CpsB phosphatase activity both in vitro and in vivo at concentrations that did not affect the growth of the bacteria. This inhibition resulted in decreased capsule synthesis in D39 and Type 1 S. pneumoniae. Furthermore, concentrations of Fascioquinol E that inhibited capsule also lead to increased attachment of pneumococci to a macrophage cell line, suggesting that this compound would inhibit the virulence of the pathogen. Interestingly, this compound also inhibited the phosphatase activity of the structurally unrelated gram-negative PTP, Wzb, which belongs to separate family of protein tyrosine phosphatases. Furthermore, incubation with Klebsiella pneumoniae, which contains a homologous phosphatase, resulted in decreased capsule synthesis. Taken together, these data provide evidence that PTPs are critical for Wzy-dependent capsule production across a spectrum of bacteria, and as such represents a valuable new molecular target for the development of anti-virulence antibacterials.